Peramalan Hasil Reaksi Asetilasi Gliserol Menjadi Triacetin Mengunakan Katalis Silika Sulfat Dari Sekam Padi Dengan Analisa Persamaan Regresi - Didik Krisdiyanto (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2014)
Glycerol is a derivative product of biodiesel transesterification process to obtain methyl ester. Glicerol derivative made from esterification of glycerol and acetic acid with the aid of a catalyst. In this study acetylation residual glycerol production of biodiesel using silica catalyst sulfate from rice husk ask with parameter ratio of reactants, reaction time, reaction temperature, the amount of catalyst and stirring speed. Results from linear regression analysis showed that the equation with reaction time variations have the highest representation of the data that is 0.9984. This is supported by forecasting analysis to predicted the results of experiments with independent variable reaction times. This indicated by the small value of the error either by using MAD, MSE, MAPE and Tracking Signals. This is mean that the equation with independent variable reaction time can be used to predict the results of a qualitative reaction.